Unequal Cities, Unequal Participation: The Effect of Income Inequality on Civic Engagement. Issue 2 (February 2019) - van Holm, Eric Joseph
Civic participation is a touchstone of American government, yet it has declined steadily over the past 50 years. Alongside changes in the relationship between American citizens and their government has been a stark increase in the levels of income and wealth concentration. While there is strong evidence that income inequality drives down participation at the national level, there have been fewer studies on the effects for local governments. This article studies the relationship between participation in departmental policy making and income inequality at the local level across the United States in a sample of small and mid-sized cities. When accounting for aspects of the government's structure, local department culture, and community demographics, income inequality has a significant, though mixed, effect on civic participation. While changes in a community's income inequality diminish the likelihood of citizens participating in government decision making, the present level of income inequality correlates with higher rates of engagement.